2022
DOI: 10.2174/1570159x19666210611095320
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Nuclear Magnetic Resonance Metabolomics Study Identifies Metabolites that Could Serve as Diagnostic Markers of Major Depressive Disorder

Abstract: Background: Evaluation of metabolites that are directly involved in the physiological process, few steps short of phenotypical manifestation, remains vital at unraveling the biological moieties involved in the development of the (MDD) and in predicting its treatment outcome. Methodology: Eight bio-fluids ( 8 urine and 8 serum samples) obtained from consenting healthy controls (HC), twenty five (25) biofluids from first episode treatment naïve MDD (TNMDD) patients and twenty (22) biofluids from treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Currently, tumor staging and prognosis evaluation methods have limitations [ 16 18 ]. However, recent advancements in metabolomics offer new opportunities for identifying novel cancer diagnostic markers and prognostic assessments [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tumor staging and prognosis evaluation methods have limitations [ 16 18 ]. However, recent advancements in metabolomics offer new opportunities for identifying novel cancer diagnostic markers and prognostic assessments [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A future study that could leverage on association study designs previously reported for genomic or metabolomic features in recruited participants could be done to identify the factors that may predict the weight gain associated with olanzapine 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…When R2Y > 0.5 and Q2>0.5, the OPLS-DA model was considered a valid model. And the closer the accumulated values of R2Y and Q2 are to 1, the more reliable the model is [ 23 ].…”
Section: Methodsmentioning
confidence: 99%